Spirituality and psychology — shared care - Kovács, Maria Júlia (O Mundo da Saúde, 2007)
The present text examines the profound relations between human beings psychical aspects and the search for spirituality. A partnership is established here, of joint search, and we also try to emphasize the specificities of each area.